Evaluasi Efektivitas Program Literasi Digital terhadap Kesadaran Privasi Data dan Etika Bermedia Sosial - Winarsih, Tutik; Resmawa, Ira Ningrum; Triono, Bambang (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Rapid digital development brings serious challenges related to personal data protection and social media ethics, especially among students who will enter the technology-based workforce. Responding to this need, the team from the YAPAN College of Economics carried out a community service program entitled "Evaluation of the Effectiveness of the Digital Literacy Program on Data Privacy Awareness and Social Media Ethics" at SMK Perdana 1 Surabaya. The purpose of this activity is to improve the digital literacy of students, teachers and school staff through an understanding of personal data protection regulations and the practice of social media ethics. The implementation methods included coordination and needs assessment, delivery of educational materials based on Law No. 27 of 2022, interactive discussions, workshops on social media privacy settings, as well as pre-test and post-test. The evaluation results showed a 45.8% increase in participants' understanding of the classification of personal data, data subject rights, and the importance of responsible digital behavior. In addition, participants responded positively with an average satisfaction score of 4.2 on a scale of 5, along with an appreciation of the relevance of the material to the needs of vocational students as prospective workers. In conclusion, the program proved to be effective in increasing legal, ethical, and digital security awareness, while making a real contribution in equipping students to face the challenges of the working world in the digital era.